Jagaddhita Family Saves Children from Violence and Exploitation: A Perspective on the Usage of the Non-Penal Policy - AAA Ngurah Tini Rusmini Gorda; I Gede Agus Kurniawan (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2020)
The purpose of this article is to examine the child protection that is integral/simultaneous and prioritizing the non-penal policy by forming and realizing the Jagaddhita family. This research is normative juridical research. The results show that in terms of penal-policy the State has provided a legal umbrella through the Law of the Republic of Indonesia No. 23 of 2002 on Child Protection as amended by the Law of the Republic of Indonesia No. 35 of 2014. However, as time goes by such Law is deemed unable to run effectively and the crime against children is increased. Establishing the Jagaddhita family as a non-penal policy is a strategic effort in eliminating any crime related to children. Such establishment is the goal of a marriage in which the marriage itself has four (4) main objectives namely Dharma, Artha, Kama, and Praja that will lead to the birth of good children.